2014
DOI: 10.7547/0003-0538-104.4.394
|View full text |Cite
|
Sign up to set email alerts
|

Needling Versus Liquid Nitrogen Cryotherapy for the Treatment of Pedal Warts

Abstract: The regression rate of the primary pedal wart was significantly higher in the needling group compared with the liquid nitrogen cryotherapy group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
10
2

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 10 publications
0
10
2
Order By: Relevance
“…Our results for clearance conflict with the findings of the only other RCT of the needling procedure by Cunningham et al . This was a smaller study of 37 participants and showed a statistically significant difference in clearance rates favouring the needling group after 12 weeks, relative to cryotherapy.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Our results for clearance conflict with the findings of the only other RCT of the needling procedure by Cunningham et al . This was a smaller study of 37 participants and showed a statistically significant difference in clearance rates favouring the needling group after 12 weeks, relative to cryotherapy.…”
Section: Discussioncontrasting
confidence: 99%
“…Our study followed the same treatment protocols as Longhurst and Cunningham, with the exception that participants in our needling group were given one treatment. Longhurst and Bristow reported a high resolution rate (38 of 45) after one needling treatment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the face of it this latest trial may not appear to be much of step forward; indeed it is not, but there are some lessons to be learned: The bright hope of needling as an effective treatment for plantar warts appears to have been somewhat dashed by this new trial. Two previous studies, a case series and a randomized trial, showed apparently promising results from this type of treatment with clearance rates of 60–70%. Altogether then, the needling story is beginning to look a bit like the duct tape story where a wave of enthusiasm followed the quirky Focht et al .…”
mentioning
confidence: 87%